REMOVAL OF AMOXICILLIN VIA DIFFERENT METHODS, EMPHASIZING REMOVAL BY BIOPOLYMERS AND ITS DERIVATIVES. AN OVERVIEW. - Rivas, Bernabe L; Aranda, Francisca (Journal of the Chilean Chemical Society, 2022)
Although pharmaceutical compounds such as antibiotics have been of great help to animals and humans, the excessive use of them have become a global problem due to the resistance of pathogens to these drugs, for this reason a series of methods have been reported that we will see below that allow to remove efficiently, economically, and environmentally friendly compounds such as antibiotics. The aim of this overview is the removal of amoxicillin via different methods, emphasizing removal by biopolymers and its derivatives.